DEVELOPMENT OF E-BOOK SUBJECT ON FLOW ENERGY AND CYCLE BIOGEOCHEMICAL AT HIGH SCHOOL - GAYUH SATRIA W (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Learning on the subjects of biology, especially in the matter of energy flow and biogeochemical cycles need for instructional media to assist students who have difficulty in understanding the biology material. Therefore, the media needs to be developed so that students learn the material easy to understand energy flow and biogeochemical cycles. One alternative is the use of electronic book. This research aimed to describe the feasibility study of media electronic book describes the results of studies and students to use media legibility of electronic books. Development of the electronic book with reference to Assure models. Media development stages include Analyze learne, State Objective, Select Methods, Media and Materials, Utilize Media and Materials, Require Learner Participation, Evaluate and revise. Results of legibility student eligibility values ​​obtained for 94.6%. Students responded positively to the use of electronic book subject Energy Flow and Recycling Biogeochemistry. Keywords: Electronic books, Assure the model development stage, Energy Flow and Recycling Biogeochemistry